(untitled) (Nigerian Journal of Pharmaceutical Research, 2020)
Background: Malaria, though preventable and treatable, remains a disease with unacceptably high mortality in Nigeria. Effective and prompt treatment of uncomplicated cases reduces progression to severe disease, development of drug resistance, and cuts the costs of the disease. Objective: To assess adherence by prescribers to recommended treatment (based on National Treatment Guideline) for uncomplicated malaria in primary health centres (PHCs) in the eight Local Government Areas (LGAs) of Bayelsa State, Nigeria. Methods: A retrospective review of case notes and prescription sheets for suspected malaria cases treated at 28 PHCs within a year of data collection was done. Relevant data about the prescribers, the patients, and the antimalarial drugs prescribed were collected and analyzed as appropriate. Results: A total of 2,303 case notes of patients attending PHCs were examined over the study period. A high proportion of malaria (1422, 61.7%) was observed among the 2,303 cases. The median age (years) of adults was 28.0 (IQR = 14), and for children of 0-5, 2.0 (IQR = 2.17). Majority of those treated were females (792, 55.7%) and children (967, 68.0%). Artemisinin-based combination therapies (ACTs) were the most prescribed antimalarials (961, 67.6%), followed by artemisinin monotherapies in 23.8% of cases. Proportion of treated cases of malaria that could be considered rational across the LGAs was 67.6%. Conclusion: Adherence of prescribers to National Treatment Guidelines of uncomplicated malaria in PHCs in Bayelsa State was below the required standard, with continued usage of obsolete agents, such as artemisinin monotherapies. Training on case management for prescribers at this level of care is urgently needed